Looking at the Local Participation of Coastal Communities in South Java, Indonesia - HANDOKO, Waluyo (International Journal of Environmental, Sustainability, and Social Science, 2023)
This study aims to describe the issues and problems of community participation related to the empowerment program entitled PKPT (Development of Strong Coastal Area) in the coastal areas. This study also discusses the importance of creating a participatory development model. This study is essential because PKPT implementation is specific, combining the top-down participation mechanism from the central government with the bottom-up mechanism, namely the northern coastal communities in South Java. The combination of the two mechanisms illustrates the complexity of issues and problems that are not simple because they involve the interests of the central government and the interests of ordinary citizens in coastal areas. Moreover, the focus of this study has yet to be widely studied by previous studies. This study uses a qualitative method applying an action research approach. The informants of the research are organizers of the coastal community, heads of village and village officials, and personnel of the Marine and Fisheries Service of Kebumen Regency in South Java. The result shows that implementing the PKPT program in coastal areas of Java, especially in Kebumen, uses both top-down and bottom-up mechanisms resulting in low participation of the community in the implementation of PKPT substantively. Thus, implicating the lack of sustainability in the empowerment program. This study presents a participatory development model that is expected to be a reference in organizing a sustainable empowerment program for the coastal areas in the future.